Order Tracking and Delivery Assisting System - Lambov, Atanas (Department of Electrical Engineering, Computer Engineering and Informatics, Faculty of Engineering and Technology, Cyprus University of Technology, 2019)
The amount of online purchases has been rapidly increasing in the last decade[1]. Nowadays people can purchase almost anything from the internet and have it delivered to their home or post office in the next few days[2]. This has resulted in the creation of ecosystem of customers, producers and delivery service providers. The growing customer needs have been met by the producers through the use of robotics and other automated equipment for the production of the goods they offer. Unfortunately, this is not the case for the delivery service providers. Their way of operation has stayed the same for the most part, especially for the delivery drivers. We believe that this should not be the case and that we can design and implement a system that can assist the delivery service providers to meet the ever-growing customer needs, and provide better overall experience for their online purchases.
Keywords: Online purchases; Delivery service providers; Customer needs